Multi-Tasking Robot using Microcontroller for Agriculture Application. Issue 1 (1st August 2022) - Sebastian Vindro Jude, P.; Kathirvel, C.; VenkateshKumar, S.; MohanKumar, R.
Abstract: With innovations in every field of our lives, agricultural field also gets impacted by technological innovations on a huge scale. Agriculture is the backbone of India. In order to support this, a multi-functioning robot is required. Smart farming aids in boosting the quality and quantity of the yields. Currently, smart agriculture is implemented to save the manpower and time of work with the help of multitasking robots. This is the advanced booming technology in the agriculture sector. However, certain considerations and approaches should be taken when designing these types of robots, taking into account the agricultural setting in which they will be used. The main aim of this research is to provide smart farming at low cost without compromising on the efficiency of the processes involved. This paper discusses the design procedure and development of an independent multitasking robot that could be applied for agricultural purpose like soil digging, sowing seeds, harvesting as well as irrigation. This robot works on solar energy and will also help in conserving non-renewable energy resources on a large scale thereby contributing towards the sustainability of our planet. With help of technologies, this idea kindles the knowledge in developing more intelligent and smart robots for the agriculture activities.